Machine learning augmented high throughput formulations - Shi, Shi Jun (Nanyang Technological University, 2023)
Material discovery holds the key to technological advancement as materials’ properties dictate their potential applications. However, conventional methods targeted at discovering new materials can be time-consuming and labour-intensive, which hinders technological advancements. There are some ways to accelerate the pace of material discovery.